Dynamic tests in the diagnosis and differential diagnosis of Cushing's syndrome. - Morris, D; Grossman, AB (2003)
Cushing's syndrome is an uncommon disorder, but one that often presents diagnostic challenges to the managing physician. Since the 1960's, dynamic tests have been a mainstay of the investigation of this disorder, both to make the diagnosis and then to identify the cause. It is in this latter role that these tests provide the greatest results, particularly in cases of ACTH-dependent disease, where defining the source accurately allows targeted surgery to the pituitary or ectopic lesions. It can, however, be a confusing area, as multiple protocols, and therefore cut-off criteria, often exist for each test, and some tests are now largely redundant. Therefore, in this article we discuss the physiological basis behind each dynamic test, review the different protocols and criteria that have been utilized, and assess how they perform. It will become clear that no single dynamic test used in this condition is 100% reliable for either the diagnosis or differential diagnosis, but the combination of test results, together with the knowledge of an endocrinologist experienced in such cases, provides the best means of correctly assessing patients with Cushing's syndrome.